2013
DOI: 10.1051/0004-6361/201321282
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of quasi-chemically homogeneous evolution of massive stars up to solar metallicity

Abstract: Context. Long soft gamma-ray bursts (LGRBs) are usually associated with the death of the most massive stars. A large amount of core angular momentum in the phases preceding the explosion is required to form LGRBs. A very high initial rotational velocity can provide this angular momentum. This velocity strongly influences the way the star evolves: it is mixed in a chemically homogeneous way and evolves directly towards the blue part of the Hertzsprung-Russell (HR) diagram from the main sequence. Aims. We have s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…The uncertainty in our modeling is then the value of this change. The values we found are consistent with the uncertainties found by Martins et al (2013) when modeling LMC WN stars using cmfgen. It should be noted that these uncertainties represent the uncertainty within the particular model and not within the modeling code itself.…”
Section: Optical Datasupporting
confidence: 91%
See 2 more Smart Citations
“…The uncertainty in our modeling is then the value of this change. The values we found are consistent with the uncertainties found by Martins et al (2013) when modeling LMC WN stars using cmfgen. It should be noted that these uncertainties represent the uncertainty within the particular model and not within the modeling code itself.…”
Section: Optical Datasupporting
confidence: 91%
“…In the Smith et al (1996) classification scheme, the spectral subtype "WNha" is used to denote a WR star with hydrogen absorption lines (see also Crowther 2007). This nomenclature has been assigned to the Galactic stars WR3 (HD9974), WR7, WR10, WR18 and WR128, the LMC stars BAT99-18 and BATAT-63, and seven SMC WRs, all of which show WR-like emission lines with some hydrogen absorption lines (see, e.g., Martins et al 2009Martins et al , 2013. cmfgen and PoWR modeling of these stars (by Marchenko et al 2004, Martins et al 2009, 2013, and Hainich et al 2015 has constrained their physical parameters 8 .…”
Section: What We Knowmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the effective photosphere-the τ = 2/3 surface-has a radius larger than the hydrostatic radius reported in the stellar evolutionary in low-metallicity environments, they may also occur in metal-rich systems. See Martins et al (2013) for more details. track, and the inferred temperature from observations, T eff, WR , is cooler than the temperature from stellar evolution calculations, T * .…”
Section: Tracks and Isochronesmentioning
confidence: 99%
“…Gies & Lambert 1992;Lyubimkov et al 2000; and more recently Hunter et al 2009 with the VLT-FLAMES survey). Martins et al (2009Martins et al ( , 2013 have even found evidence for the existence of stars in which mixing is so efficient that they are quasi-homogeneous.…”
Section: Introductionmentioning
confidence: 99%